Metabolic syndrome risk factor associations with clinical, functional and cognitive outcomes during the first year of treatment in schizophrenia spectrum disorders - Luckhoff, Hilmar Klaus (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.